Insights gained from gene therapy in animal models of retGC1 deficiency - Boye, Shannon E. (Frontiers in Molecular Neuroscience, 2014)
Vertebrate species possess two retinal guanylate cyclases (retGC1 and retGC2) and at least two guanylate cyclase activating proteins (GCAPs), GCAP1 and GCAP2. GCAPs function as Ca2+ sensors that regulate the activity of guanylate cyclases. Together, these proteins regulate cGMP and Ca2+ levels within the outer segments of rod and cone photoreceptors. Mutations in GUCY2D, the gene that encodes retGC1, are a leading cause of the most severe form of early onset retinal dystrophy, Leber congenital amaurosis (LCA1). These mutations, which reduce or abolish the ability of retGC1 to replenish cGMP in photoreceptors, are thought to lead to the biochemical equivalent of chronic light exposure in these cells. In spite of this, the majority of LCA1 patients retain normal photoreceptor laminar architecture aside from foveal cone outer segment abnormalities, suggesting they may be good candidates for gene replacement therapy. Work began in the 1980s to characterize multiple animal models of retGC1 deficiency. Thirty four years later, all models have been used in proof of concept gene replacement studies towards the goal of developing a therapy to treat GUCY2D-LCA1. Here we use the results of these studies as well as those of recent clinical studies to address specific questions relating to clinical application of a gene therapy for treatment of LCA1.